RETRACTED: CAR-NK Cell: A New Paradigm in Tumor Immunotherapy - Marofi, Faroogh; Al-Awad, Alaa S.; Sulaiman Rahman, Heshu; Markov, Alexander; Abdelbasset, Walid Kamal; Ivanovna Enina, Yulianna; Mahmoodi, Mahnaz; Hassanzadeh, Ali; Yazdanifar, Mahboubeh; Stanley Chartrand, Max; Jarahian, Mostafa (Frontiers in Oncology, 2021)
The tumor microenvironment (TME) is greatly multifaceted and immune escape is an imperative attribute of tumors fostering tumor progression and metastasis. Based on reports, the restricted achievement attained by T cell immunotherapy reflects the prominence of emerging other innovative immunotherapeutics, in particular, natural killer (NK) cells-based treatments. Human NK cells act as the foremost innate immune effector cells against tumors and are vastly heterogeneous in the TME. Currently, there exists a rapidly evolving interest in the progress of chimeric antigen receptor (CAR)-engineered NK cells for tumor immunotherapy. CAR-NK cells superiorities over CAR-T cells in terms of better safety (e.g., absence or minimal cytokine release syndrome (CRS) and graft-versus-host disease (GVHD), engaging various mechanisms for stimulating cytotoxic function, and high feasibility for ‘off-the-shelf’ manufacturing. These effector cells could be modified to target various antigens, improve proliferation and persistence in vivo, upturn infiltration into tumors, and defeat resistant TME, which in turn, result in a desired anti-tumor response. More importantly, CAR-NK cells represent antigen receptors against tumor-associated antigens (TAAs), thereby redirecting the effector NK cells and supporting tumor-related immunosurveillance. In the current review, we focus on recent progress in the therapeutic competence of CAR-NK cells in solid tumors and offer a concise summary of the present hurdles affecting therapeutic outcomes of CAR-NK cell-based tumor immunotherapies.